Analysis of Science Learning Outcomes on Matter and Its Changes in Seventh-Grade MTs Students Reviewed from Gender Differences - Az-Zahro, Fatimah; Nugraheni, Dian; Az-Zahro, Aisyah; Fitriyah, Isnanik Juni; Mulyati, Yayuk; Hamimi, Erti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study investigates science learning outcomes on the topic Matter and Its Changes among seventh-grade students at MTs, with a focus on gender differences. Using a descriptive survey method, the entire population of 77 students (two male classes and two female classes) was involved. Data were collected through post-tests, questionnaires, observations, and interviews, and analyzed quantitatively using the Mann-Whitney U test. The results show that female students had significantly higher average learning outcomes (64.04) compared to male students (45.50). Further analysis revealed that female students performed better at cognitive levels C3, C4, and C5, as well as across all subtopics. Qualitative findings from teacher interviews suggest that this difference is consistent and may be attributed to female students’ ambition and logical reasoning, as observed in class. However, questionnaire data indicate that male students report higher self-confidence. The study concludes that gender differences significantly influence science learning outcomes, with implications for instructional strategies and gender-responsive teaching practice